O filtro da repercussão geral nos recursos extraordinários por meio da análise dos temas julgados pelo Supremo Tribunal Federal - Madruga, Tatiana Cláudia Santos Aquino (2015)
Since the creation of the Supreme Court, the Court suffers from innumerable amount of processes that cram its agenda, most of them dealing with issues with little general importance. This situation has created the need to build mechanisms to prevent the causes without greater relevance to reach the Court. Attempts as the institution of the relevant complaint, the possibility of a monocratic judgment by the rapporteur and, more recently, with the promulgation of the 1988 Constitution, the creation of the Superior Court of Justice, which withdrew from the jurisdiction of the Supreme the judgment of infraconstitutional causes via resource extraordinary, were not enough to slow the crisis. It was necessary the development of new mechanisms to stop the rise of so many processes. That's when, through Amendment nº 45/2004, was created the appeal filtering institute called general repercussion. With foresight and characteristics arranged in the Constitution and in the ordinary legislation, the institute was treated in our system with the use of indeterminate concepts, making it impossible, a priori, their slimmer definition. It was up to the Supreme Court, in the analysis of the case, to evaluate what is important from an economic, social, political and legal point of view that goes beyond the subjective interests of the cause. Through the analysis of the general repercussion precedents issued by the Supreme Court, we will seek to demarcate the scope of the concepts of relevant questions from an economic, social, political and legal point of view from the perspective of the Constitutional Court, trying to define these uncertain terms, in order to help legal professionals in the arduous task of knowing objectively as possible when a cause holds or not the general repercussion. We will analyze also whether the legislative technique of using indeterminate concepts in the definition of general repercussion allows the analysis of the appeals 8with discretion by the Supreme Court or whether this is only a liberty of interpretation of indeterminate concepts according to the case.